2014
DOI: 10.1155/2014/301469
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Two Different Ankle-Foot Orthoses on Gait of Patients with Acute Hemiparetic Cerebrovascular Accident

Abstract: Objective. To compare the effects of two types of ankle-foot orthoses on gait of patients with cerebrovascular accident (CVA) and to evaluate their preference in using each AFO type. Design. Thirty individuals with acute hemiparetic CVA were tested without an AFO, with an off-the-shelf carbon AFO (C-AFO), and with a custom plastic AFO (P-AFO) in random order at the time of initial orthotic fitting. Gait velocity, cadence, stride length, and step length were collected using an electronic walkway and the subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 27 publications
2
10
0
1
Order By: Relevance
“…These types of elements have proven to be very useful, significantly improving the dynamics with which the gait exercise is performed [15][16][17]. Studies show that regardless of the material and the type of AFO used, the measurable parameters for gait exercise (cadence, joint angles, balance) do not differ from each other, the most important being the comfort and security that these elements confer to the individual at the time of choosing them.…”
Section: Physical Disabilities -Therapeutic Implicationsmentioning
confidence: 99%
“…These types of elements have proven to be very useful, significantly improving the dynamics with which the gait exercise is performed [15][16][17]. Studies show that regardless of the material and the type of AFO used, the measurable parameters for gait exercise (cadence, joint angles, balance) do not differ from each other, the most important being the comfort and security that these elements confer to the individual at the time of choosing them.…”
Section: Physical Disabilities -Therapeutic Implicationsmentioning
confidence: 99%
“…Putting on an ankle orthosis has a positive impact on the gait variables of hemiplegic stroke survivors and brings about significant changes in the variables, including gait ve-locity, gait asymmetric index, and functional balance control [17], as well as improvements in overall gait velocity, effectiveness and gait pattern [18]. In addition, it was reported that the use of an ankle orthoses in stroke survivors increased the stability of the ankle joint in the stance phase, which would lead to the increase in gait velocity [19].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was reported that the use of an ankle orthoses in stroke survivors increased the stability of the ankle joint in the stance phase, which would lead to the increase in gait velocity [19]. In addition, Rao et al [17] noted that putting on an ankle orthosis greatly improved gait velocity, step length, stride length and double support time.…”
Section: Discussionmentioning
confidence: 99%
“…Main difference between AFOs was probably related to muscular activity. Noel Rao et al [30] compared the effects of two types of AFO on gait of patients with stroke and evaluated their preference in using each AFO type design. Thirty individuals with acute hemi paretic CVA were tested without an AFO, with an off-the-shelf carbon AFO (C-AFO), and with a custom plastic AFO (P-AFO) in random order at the time of initial orthotic fitting.…”
Section: Temporal-spatial Gait Parametersmentioning
confidence: 99%